The incidence of body dissatisfaction and its association with the predictors of the female athlete triad among female athletes in weight-sensitive sports - Reyes, Rianne Danelle H. 2002-
Competitive sports put immense pressure over athletes to produce the best performance possible. Female athletes are believed to be more vulnerable to body dissatisfaction (BD) as they are more aware of the aesthetic appearance of their body. Specifically, female athletes who play in weight-sensitive sports like cheerleading, swimming, and taekwondo are more likely to experience BD as weight is a significant performance indicator in their fields. As a result, they may fall into unhealthy weight control practices like disordered eating or overtraining. One condition that may emerge is that of the Female Athlete Triad (FAT) or the interrelation of low energy availability, menstrual dysfunction, and low bone mineral density. This study aims to find the prevalence of BD and predictors of FAT among female athletes in weight-sensitive sports, and the relationship of BD with each individual predictor. Forty-seven (47) female athletes from the cheerleading, swimming, and taekwondo teams of a particular university in Quezon City to participate in the study. The results show that BD and low bone mineral density are prevalent among female athletes in weight-sensitive sports. It is found that the relationship of BD with energy availability is weak. Meanwhile, the relationship between BD and menstrual function, and bone density is statistically insignificant